Astrocytes in the regulation of cerebrovascular functions. Issue 4 (15th October 2020) - Cohen‐Salmon, Martine; Slaoui, Leila; Mazaré, Noémie; Gilbert, Alice; Oudart, Marc; Alvear‐Perez, Rodrigo; Elorza‐Vidal, Xabier; Chever, Oana; Boulay, Anne‐Cécile
Abstract: Astrocytes are the most numerous type of neuroglia in the brain and have a predominant influence on the cerebrovascular system; they control perivascular homeostasis, the integrity of the blood–brain barrier, the dialogue with the peripheral immune system, the transfer of metabolites from the blood, and blood vessel contractility in response to neuronal activity. These regulatory processes occur in a specialized interface composed of perivascular astrocyte extensions that almost completely cover the cerebral blood vessels. Scientists have only recently started to study how this interface is formed and how it influences cerebrovascular functions. Here, we review the literature on the astrocytes' role in the regulation of the cerebrovascular system. We cover the anatomy and development of the gliovascular interface, the known gliovascular functions, and molecular factors, the latter's implication in certain pathophysiological situations, and recent cutting‐edge experimental tools developed to examine the astrocytes' role at the vascular interface. Finally, we highlight some open questions in this field of research. Main Points: Astrocytes form a specific interface with brain blood vessels. We describe the anatomy, development, and properties of the astrocytic perivascular compartment. We provide an overview of the astrocytes' role in regulating vascular functions.